2014
DOI: 10.1016/j.dnarep.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK phosphorylation of RPA32 Ser4/Ser8 regulates replication stress checkpoint activation, fork restart, homologous recombination and mitotic catastrophe

Abstract: Genotoxins and other factors cause replication stress that activate the DNA damage response (DDR), comprising checkpoint and repair systems. The DDR suppresses cancer by promoting genome stability, and it regulates tumor resistance to chemo- and radiotherapy. Three members of the phosphatidylinositol 3-kinase-related kinase (PIKK) family, ATM, ATR, and DNA-PK, are important DDR proteins. A key PIKK target is replication protein A (RPA), which binds single-stranded DNA and functions in DNA replication, DNA repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 61 publications
5
105
0
Order By: Relevance
“…In response to replication stress, single-stranded DNA (ssDNA)-coating trimeric RPA protein is recruited and phosphorylated at multiple sites, with RPA32 S4/8 being found in the most hyperphosphorylated form of the protein (18). We observed an increase in phosphorylated RPA upon gemcitabine þ CHK1i treatment but not with either agent alone ( Supplementary Fig.…”
Section: Chk1 Inhibition Triggers Global Replication Stress By Deregumentioning
confidence: 85%
“…In response to replication stress, single-stranded DNA (ssDNA)-coating trimeric RPA protein is recruited and phosphorylated at multiple sites, with RPA32 S4/8 being found in the most hyperphosphorylated form of the protein (18). We observed an increase in phosphorylated RPA upon gemcitabine þ CHK1i treatment but not with either agent alone ( Supplementary Fig.…”
Section: Chk1 Inhibition Triggers Global Replication Stress By Deregumentioning
confidence: 85%
“…Mutated Ser33A, Ser4/Ser8 and Thr21A phosphorylation sites in RPA2 lead to defective recovery from replication stress (Ashley et al, 2014;Olson et al, 2006). Decreased BCAS2 affects the phosphorylation of RPA2 Ser4/ Ser8 (Wan and Huang, 2014), which is phosphorylated after Thr21 and Ser33 phosphorylation (Anantha et al, 2007;Liu et al, 2012).…”
Section: Bcas2 Functions In Mouse Zygotes Through the Rpa Complexmentioning
confidence: 99%
“…For example, the S4/8A mutant is defective in Chk1, Mre11 and TopBP1 phosphorylation in response to etoposide [98]. Recently, it was shown that cells expressing the S4/8A mutant restart replication prematurely during the recovery from etoposide-induced DNA damage, indicating a defect in sustaining the proper checkpoint response [107]. Cells lacking DNA-PKcs or expressing a kinase-inactive DNA-PKcs mutant also had decreased Chk1 phosphorylation, thereby implicating DNA-PK in ATR activation.…”
Section: Rpa Phosphorylation and The Ddrmentioning
confidence: 99%